26 Using combination of high-fat diet and high-dose streptozotocin to develop an in vivo model of diabetic cardiomyopathy. (16th October 2019) - Kerrigan, L; Edgar, K; Russell-Hallinan, A; Grieve, D; Watson, C
Abstract : Heart failure (HF) is growing at alarming rate worldwide, largely due to increased prevalence of obesity and type-2 diabetes mellitus (T2DM). It is recognised that clinical prognosis for DM patients diagnosed with HF, is significantly worse than that of non-DM HF patients. Diabetic cardiomyopathy (DCM) is defined as the presence of diabetic-associated diastolic dysfunction in the absence of explicit coronary artery disease or other typical cardiovascular risk factors. DCM significantly increases the risk of chronic HF, but is commonly considered an underlying condition with subclinical cardiac dysfunction, and therefore is frequently underdiagnosed. An effective strategy for prevention and treatment of DCM has yet to be established. Therefore it is imperative we identify clear pathophysiological mechanisms of DCM so as to ultimately determine potential diagnostic advancements and therapeutic targets. Investigating pathological pathways involved in development of DCM is impossible without the foundation of reliable experimental models. Inducing experimental T2DM in vivo is commonly accomplished via delivery of streptozotocin (STZ) or the use of high-fat diet (HFD). Standard STZ induction produces a metabolic phenotype representative of T2DM with consistent cardiac fibrosis and diastolic dysfunction, but also causes acute pancreatic inflammation more in line with type-1 DM; limiting the suitability of the model. HFD induction is more relevant in terms of obesity-related DM, with more chronic progression of pathological features; however it does not develop consistent diastolic dysfunction. Therefore, the objective of this study was to characterise an improved experimental model of T2DM with reliable development of DCM characteristics, more reflective of human disease. Several groups use a hybrid model combining HFD with a single dose of STZ (opposed to multiple doses). However, the precise protocols used are variable and poorly characterised with regard to cardiac fibrosis and diastolic dysfunction. The majority of previous studies deliver a 50–100 mg/kg dose of STZ following 3–4 weeks of HFD. We fed 4 week old, male C57BL6 mice HFD for an overall period of 10 months; experimental groups received 100 mg/kg STZ (or vehicle only) at either week 8 or week 12 of the diet. Mice were monitored in parallel with untreated mice on normal diet throughout the study. Weights were recorded weekly, blood glucose levels and cardiac function (measured by echocardiography) were recorded monthly. At the end of the study, mice were sacrificed at which point blood and excised heart tissue were collected and analysed. Results of this study indicate that a single dose of STZ at week 8 of the HFD is adequate to induce T2DM, providing evidence of cardiac fibrosis and diastolic dysfunction progression. We believe the data generated represents a reliable model of DCM and we propose that this model could be employed as the basis of future mechanistic and therapeutic studies.